S1 Guidelines for the Kaposi Sarcoma. (3rd June 2022) - Esser, Stefan; Schöfer, Helmut; Hoffmann, Christian; Claßen, Johannes; Kreuter, Alexander; Leiter, Ulrike; Oette, Mark; Becker, Jürgen C.; Ziemer, Mirjana; Mosthaf, Franz; Sirokay, Judith; Ugurel, Selma; et al.
Summary: Kaposi's sarcoma (KS) is a rare, malignant, multilocular vascular disease originating from lymphatic endothelial cells that can primarily affect the skin and mucous membranes, but also the lymphatic system and internal organs such as the gastrointestinal tract, lungs or liver. Five epidemiological subtypes of KS with variable clinical course and prognosis are distinguished, with increased incidence in specific populations: (1) Classical KS, (2) Iatrogenic KS in immunosuppression, (3) Endemic (African) lymphadenopathic KS, (4) Epidemic, HIV‐associated KS and KS associated with immune reconstitution inflammatory syndrome (IRIS), and (5) KS in men who have sex with men (MSM) without HIV infection. This interdisciplinary guideline summarizes current practice‐relevant recommendations on diangostics and therapy of the different forms of KS. The recommendations mentioned in this short guideline are elaborated in more detail in the extended version of the guideline (online format of the JDDG).